Pengaruh Green Accounting dan Kinerja Lingkungan Terhadap Profitabilitas Perusahaan Pertambangan di Bursa Efek Indonesia Tahun 2019-2023) - Yona Okterianda; Destia Pentiana; Nurmala Nurmala (eCo-Fin, 2025)
This study aims to analyze the impact of green accounting practices and environmental performance on profitability, measured by the return on assets (ROA) ratio. A quantitative approach is used, relying on secondary data sources. The population consists of 45 mining companies listed on the Indonesia Stock Exchange from 2019 to 2023, and a sample of 11 companies was selected through purposive sampling. Data collection was carried out using documentation, drawing from financial statements, annual reports, and sustainability reports of the sampled companies for the 2019-2023 period. The data were then analyzed with SPSS version 25. In this study, green accounting is assessed through environmental costs, while environmental performance is evaluated using the PROPER rating. Statistical tests conducted include descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing. The findings indicate that green accounting has a significant negative effect on company profitability, while environmental performance shows no impact on profitability individually, though both variables together do influence profitability